Exam invigilation scheduling system for UiTM Malacca Jasin Campus / Maizatul Akmam Mustapa - Mustapa, Maizatul Akmam (2015)
The final exam invigilation schedule in UiTM Malacca Jasin campus is prepared by UiTM Pulau Pinang Scheduling System, where all the factors and information of lecturers’ constraint being sent there by the Examination Unit. There is always a delay in waiting for the invigilation schedule to be announced. If there are any changes of the schedule after the schedule is generated, the schedule will not be updated in the system. The schedule changing process is done manually by form. The Exam Invigilation Scheduling System aims to own a scheduling system in the campus and reduce the time used in creating the invigilation schedule. To solve the invigilation scheduling problem, constraint based technique with rule based approach is used to find the optimal solution. Rule based technique is used in searching method and involve knowledge base as the data constraint store. In developing the project, software prototyping model was used which involves of the preliminary investigation, requirement definition, system design, system development, system testing and system prototype phase. Two interviews have been conducted as data collection method. The findings of the project include the system requirements and rules. There were ten rules involved in creating the invigilation schedule. The project does not assist in changing the invigilator assigned in the invigilation schedule. Thus, it is recommended to provide function that allows the application of schedule changes for future works.